Impact of Mobile Learning on Students' Achievement Results - Blanka Klimova (MDPI AG, 2019)
Today, mobile learning is a well-established methodology thanks to its countless benefits such as accessing learning content anytime and anywhere, adjusting the content to students’ needs, and timely feedback. The purpose of this pilot study is to illustrate that foreign language learning supported by a personalized smartphone app can be effective in the enhancement of university students’ performance by implementing smartphone app learning in a continuous assessment. The methodology is a case study analysis of students’ needs, with statistical processing of the collected data. The results reveal that foreign language learning, particularly studying and revising English vocabulary and phrases via smartphones is effective in the enhancement of university students’ performance. However, such learning must be designed around students’ needs and continuously facilitated by a teacher. Only then can it contribute to positive learning outcomes. In addition, the results also confirm that mobile learning can serve as an appropriate complementary method to other forms of course delivery. Further research should extend the mobile app to the Apple platform and iOS.